2011
DOI: 10.1007/s00300-011-1136-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of loggers on the foraging effort and chick-rearing ability of parent little auks

Abstract: We studied the effects of loggers attached to chick-rearing little auks (Alle alle) on their daily time budget (proportion of time spent in the colony and at sea), foraging activity (duration and proportion of long and short foraging flights), chick provisioning rate and their growth and development on Spitsbergen. We found that experimental parent birds performed shorter but more frequent long foraging flights and reduced the frequency of short foraging flights. They spent more time at the colony and reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 53 publications
3
18
0
Order By: Relevance
“…Our results correspond with those of previous studies on Little Auks, which showed that in poor foraging habitat conditions, chick feeding frequency and chick body mass substantially decreased Kidawa et al 2015). A lower body mass has been previously documented in chicks with parents that had their feathers clipped or carried data loggers Kidawa et al 2012). A limitation of our study is the fact that the additional acute stress caused by implanting pellets is indistinguishable from the exogenous corticosterone dissolving from the pellet.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results correspond with those of previous studies on Little Auks, which showed that in poor foraging habitat conditions, chick feeding frequency and chick body mass substantially decreased Kidawa et al 2015). A lower body mass has been previously documented in chicks with parents that had their feathers clipped or carried data loggers Kidawa et al 2012). A limitation of our study is the fact that the additional acute stress caused by implanting pellets is indistinguishable from the exogenous corticosterone dissolving from the pellet.…”
Section: Discussionsupporting
confidence: 90%
“…Nonetheless, in the experiment with corticosterone-implanted parents, we observed no significant increase in the feeding rate of the untreated partner. However, the delivery rate by the partners was one of the highest observed in the studied colony and other Little Auk colonies to date (Stempniewicz and Jezierski 1987;Jakubas et al 2007;Welcker et al 2009;Karnovsky et al 2010;Kwasniewski et al 2010;Grémillet et al 2012;Kidawa et al 2012;Hovinen et al 2014;Kidawa et al 2015). It is likely that these birds provisioned chicks at near their maximal rates.…”
Section: Discussionmentioning
confidence: 99%
“…However, a similar bias towards longer foraging trips was also observed in little auks equipped with the same type of GPS devices in Spitsbergen [ 16 ]. Devices attached to diving seabirds increase hydrodynamic drag [ 63 ], and has been shown to affect trip duration in some species, including little auks [ 64 , 65 ]. Overall, we recommend that future little auk GPS-tracking studies use smaller/lighter tags, to ensure the smallest possible impact on the birds.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we compared the foraging-trip duration of equipped birds with that of nonequipped ones. Foraging-trip duration has been shown to be a reliable proxy for foraging effort in Cape Gannets (Pichegru et al 2007) and is regularly used to assess the effects of tagging on seabirds (Wilson et al 1986, Phillips et al 2003, Kidawa et al 2012. To do so, we monitored the attendance of both partners (every hour from sunrise to sunset) on 14 independent nests where chicks were reared during 10 days.…”
Section: Instrument Effectsmentioning
confidence: 99%